Computer-based Training and Electronic Publishing in the Health Sector: Tools and Trends - Schulz, S.; Schrader, U.; Klar, R. (Methods of Information in Medicine, 1997)
CBT (computer-based training) applications and hypermedia publications are two different approaches to the utilisation of computers in medical education.Medical CBT software continues to playa minor role in spite of the increasing availability, whereas hypermedia have become very popular through the World Wide Web (WWW). Based on the HTML format they can be designed by non-programmers using inexpensive tools while the production of CBT applications requires programming expertise. HTML documents can be easily developed to be distributed by a web-server or to run as local applications.In developed countries CBT and hypermedia have to compete with an abundance of printed or audio-visual media and a wealth of lectures, conferences, etc., whereas in developing countries these media are scarce and expensive. Here CBT programs, and hypermedia publications in particular, may be a cost-effective way to improve quality of education in the health sector.
Keywords: Hypermedia; Computer-based Training; Medical Education; Developing Countries